1981
DOI: 10.1111/j.1365-2672.1981.tb01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Cellulolytic Bacteria from Activated Sludge

Abstract: Cellulolytic aerobic bacteria were isolated from activated sludge systems. Of the media tested for enumeration, only filter paper media gave reliable counts. Five isolates were studied further for characterization. It was found that one strain (DK) belonged to the genus Cellulomonas. The other four strains expressed similarity to the genus Pseudomonas. The different characteristics that were studied, however, do not permit them to be identified with any recognized species. Based on certain characters we believ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
1
0
2
Order By: Relevance
“…Cellulose has been indicated as a major component (25%–30%) of the particulate fraction of municipal wastewater due to the direct discharge of toilet paper (Ramasamy, Meyers, Bevers, & Verachtert, ; Ruiken, Breuer, Klaversma, Santiago, & van Loosdrecht, ). Theoretical estimation of the influent cellulose using the per capita annual toilet paper consumption in western Europe (14 kg/capita) indicated that cellulose is 40% of the influent solid mass (Ruiken et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose has been indicated as a major component (25%–30%) of the particulate fraction of municipal wastewater due to the direct discharge of toilet paper (Ramasamy, Meyers, Bevers, & Verachtert, ; Ruiken, Breuer, Klaversma, Santiago, & van Loosdrecht, ). Theoretical estimation of the influent cellulose using the per capita annual toilet paper consumption in western Europe (14 kg/capita) indicated that cellulose is 40% of the influent solid mass (Ruiken et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Es importante por lo tanto, estandarizar un método aplicable a los actinomicetos celulolíticos que nos permita correlacionar el tamaño de los halos de hidrólisis con la actividad enzimática correspondiente. Sin embargo, la degradación del papel filtro es un méto-do alternativo, que permitió, por ejemplo a Ramasamy et al (1981) seleccionar cepas celulolíticas de Pseudomonas a partir de lodos. llaron significativos niveles de celulasas extracelulares en hongos silvestres aislados de nuestro medio.…”
Section: Discussionunclassified
“…Los cultivos se incubaron a 45 o C en el caso del género Streptomyces, y a 50 o C si se trataba del género Thermomonospora hasta los 5 días; y se examinaron diariamente para evaluar la capacidad degradativa sobre el papel filtro (Ramasamy, 1981 De las cepas que presentaron elevadas actividades según los criterios establecidos anteriormente, se seleccionaron 10 para las determinaciones cuantitativas de las celulasas. Con este fin, se inocularon 40 x 10 6 esporas por 100 ml de medio mínimo de Crawford y McCoy (1972) más CMC y lactosa al 1% como inductores y Tween 80 (Sigma) 0,2%.…”
Section: Determinación Cualitativa De La Actividad Celulolíticaunclassified